The inter-connections between self-harm and aggressive behaviours: A general network analysis study of dual harm - Shafti, Matina; Steeg, Sarah; de Beurs, Derek; Pratt, Daniel; Forrester, Andrew; Webb, Roger T.; Taylor, Peter James (Frontiers in Psychiatry, 2022)
Dual harm is the co-occurrence of self-harm and aggression during an individual’s lifetime. This behaviour is especially prevalent within criminal justice and forensic settings. The forms of aggression that should be included in the definition of dual harm have not yet been established. This study aimed to use network analysis to inform an evidence-based definition of dual harm by assessing the relationship between self-harm and different forms of aggressive behaviour in young people (N = 3,579). We used data from the Avon Longitudinal Study of Parents and Children (ALSPAC). Results revealed low correlations between the variables, leading to sparse network models with weak connections. We found that when separated into their distinct forms, aggressive acts and self-harm are only weakly correlated. Our work provides preliminary evidence to assist in understanding and managing dual harm within clinical and forensic settings and informs recommendations for future research.